What Anchors Semiosis : How Descartes Changed the Subject - Champagne, Marc (Recherches sémiotiques / Semiotic Inquiry, 2008)
The goal of this article is twofold. First, it revises the historiographic partition proposed by John Deely in Four Ages of Understanding (2001) by arguing that the moment marking the beginning of philosophical Modernity has been vividly recorded in Descartes’ Meditations on First Philosophy with the experiment with the wax. Second, an upshot of this historical study is that it helps make sense of Deely’s somewhat iconoclastic use of the words “subject” and “subjectivity” to designate mind-independent worldly things. The hope is that successfully accomplishing these twin tasks will give semiotic inquiry a better appreciation of its own history, as well as resources genial to furthering its ongoing development.